Empirical test of the participation paradox in conservation and development - Nabin Baral; Joel T. Heinen; Marc J. Stern (Conservation Science and Practice)
Abstract Local participation has been greatly promoted to accomplish conservation and development goals globally, but the participation paradox, in which those empowered to participate fail to do so, has rarely been thoroughly scrutinized. Here we test the participation paradox with empirical data of 234 local decision‐makers' participation in a decision‐making forum, Conservation Area Management Committees, in the Annapurna Conservation Area, Nepal. Using an explanatory sequential mixed methods design, both quantitative and qualitative data were collected in 2013 and 2016, analyzed, interpreted, and integrated. Women, minorities, younger members, and non‐elected members participated significantly less in decision‐making than men, older members, and elected members and those with leadership roles and longer tenures on the committees. Qualitative analyses revealed five major themes for motivation to participate: influence in the community; personal incentives; conservation; improving access to natural resources; and feelings of accomplishment. Key constraints to participation included hardships and competing tasks; lack of incentives; perceptions of limited agency; disinterest; and emotional burdens. Participation motivations and constraints varied by gender, social group, and membership types. We discuss the theoretical and practical implications of these results for participatory approaches to conservation and sustainable development in general and the governance of protected areas in particular.